Nutritional characteristics of meat from lambs fed diets containing mulberry hay - Cirne, L. G. A.; Sobrinho, A. G. S. [UNESP]; Oliveira, E. A. [UNESP]; Carvalho, G. G. P.; Moreno, G. M. B.; Valenca, R. L. [UNESP]; Almeida, F. A. [UNESP]; Endo, V [UNESP]; Zeola, N. M. B. L. [UNESP] (South African Journal Of Animal Sciences, 2019)
The objective of this study was to evaluate the nutritional characteristics of meat from lambs fed diets containing 0%, 12.5% and 25.0% (dry matter (DM)) mulberry hay as a substitute for the concentrate. Twenty-four feedlot Ile-de-France lambs with an average age of 60 days and bodyweight (BW) of 15 kg were fed in individual stalls and slaughtered at 32 kg BW, at approximately 130 days old. The chemical composition of the experimental diets contained, respectively, 584.4, 569.4 and 571.8 g DM/kg; 188.8, 185.1 and 184 g crude protein (CP)/kg and 29.9, 29.5 and 25.5 Mcal/kg DM for the mulberry hay inclusion levels of 0%, 12.5% and 25.0%, with a dietary forage to concentrate ratio of 50 : 50. The chemical composition of the meat was 757.9 g moisture/kg DM, 208.6 g CP/kg DM, 22.9 g crude fat/kg DM and 10.5 g ash/kg DM. Cholesterol concentration (36.07 mg/100 g) in the meat was not influenced by mulberry hay inclusion of the diet. An increase was observed in the concentrations of saturated pentadecanoic, heptadecanoic and arachidic acids; monounaturated heptadecenoic acid; and polyunsaturated alpha-linolenic, gamma-linolenic and eicosapentaenoic acids. Nervonic and conjugated linoleic acid (CLA) concentrations responded quadratically, representing 3.7 g/kg and 5.9 g/kg of the meat when mulberry hay was included at 16.98% and 12.56%. Omega-3 acid concentrations increased, while the omega-3 : omega-6 ratio decreased in the meat of mulberry hay-fed animals. Inclusion of mulberry hay in lamb diets increases the amount of desirable fatty acids in their meat, whose nutritional characteristics are improved.
Keywords: Chemical composition; fatty acids; feedlot; sheep meat